Getting of structurally-colored alkyd resin and its properties - Маслош, Владимир Зиновьевич; Алексеева, Наталья Николаевна; Маслош, Ольга Владимировна; Клименко, Геннадий Алексеевич (Eastern-European Journal of Enterprise Technologies, 2012)
Colored polymers are prepared by mixing the polymer material and the dye. To obtain uniform color it is necessary to grind the dye. Some dyes have such properties as water receptivity and formation of agglomerates, which affect negatively the coloring process and require additional equipment. Because of microcracks and tinges in pigments, some difficulties arise, when combining polymers with polymer matrix. That reduces the properties of colored polymers. The method of structural dyeing of polymers can obviate these difficulties. The aim of our work is to study the patterns of obtaining the structurally-colored alkyd resin, modified with oil. The scheme of obtaining structural-colored modified resin can be represented as follows. First, let us carry out the interesterification of pentaerythritol by oil. On the second stage, we add azo pigment to interesterificator. Then, we add the phthalic anhydride and glycerin and carry out the polycondensation up to the specified acid number. The possibility of obtaining structural-colored alkyd resin modified with oil was shown. The structure of structurally-colored alkyd resin modified with oil was proved by IR spectroscopy and kinetic data obtained.